Study of the effect of commercial kinetic inhibitors on gas-hydrate formation by DSC: non-classical structures? - Malaret,F; Dalmazzone,C; Sinquin,A (2008)
A HP micro DSC-VII from SETARAM was used to study the efficiency and mechanism of action of commercial kinetic inhibitors for gas-hydrate formation in drilling fluids (OBM). The main objective was to find a suitable and reliable method of screening for these chemicals. The DSC technique consists in monitoring the heat exchanges, due to phase changes (here hydrate formation or dissociation), either versus time at constant temperature or versus temperature during a heating or cooling program. All products showed a gas hydrate dissociation temperature (at a given pressure) that matched with theoretical and previously published data. Nevertheless, for some additives two thermal signals were observed on the thermograms, one that corresponds to the theoretical value and another at a higher temperature (about +4°C). This second peak is insensitive to the heating rate applied for the dissociation, but the areas ratio (1stpeak/2nd peak) changes with the additive concentration and with the driving force applied during the hydrate formation. Additionally, additive/water and additive/water/THF systems were tested. In each case, two dissociation peaks were also measured. The results allow us to disregard any kinetic effects bonded to this thermal phenomenon, and lead us to infer that some additives may induce non-classical crystalline structures of gas hydrates. To verify these results, crystallographic and spectroscopic experiments must be performed. The stabilities of these new compounds are under study.